Knowledge, Attitude and Acceptability of the Human Papilloma Virus Vaccine and Vaccination Among University Students in Indonesia - Khatiwada, Madan; Kartasasmita, Cissy; Mediani, Henny Suzana; Delprat, Christine; Van Hal, Guido; Dochez, Carine (Frontiers in Public Health, 2021)
Introduction: Cervical cancer, major outcome of persistent HPV infection, is the third most common cancer among women worldwide and claimed around 311,000 women lives in 2018. Majority of these deaths eventuated in low- and middle-income countries (LMICs). In LMICs, where cervical cancer screening coverage is low, HPV vaccine can be a promising tool to prevent HPV infections and thus avert cervical cancer cases. In Indonesia, cervical cancer is the second most common cancer and HPV vaccination demonstration programs are being carried out in several provinces, but the HPV vaccines is not yet introduced nationally. Since students are an important source of information for the community, and medical and nursing students are future healthcare professionals, this research study explored knowledge, attitude and acceptability of HPV vaccine among university students in Indonesia. Methodology: A self-administered online questionnaire was used to assess the knowledge, attitude and willingness of university students towards HPV vaccination. Result: In total 433 students from Medical, Nursing, Social Sciences and other faculties participated in the survey. It was identified that more than 90% of the students were aware about cervical cancer and HPV, but only 68% knew about HPV vaccine before participating in the study. In spite of having average knowledge on HPV vaccine, students showed high willingness to receive the vaccine (95.8% acceptance rate). They believed that HPV vaccine is safe and effective, and will protect from HPV infection. High cost and lack of circulation of adequate information on HPV related topics were pinpointed as the potential barriers for HPV vaccine uptake in Indonesia. Conclusion: Despite high willingness for HPV vaccine uptake among students, it is necessary to impart education on HPV vaccine-related subjects to the Indonesian students through awareness and training programs, and by upgrading academic curriculum on vaccination for long term sustainability of HPV vaccination program.